The Effectiveness Of Massage and Baby SPA (Swim) on the Suitability of the Development of Infants Aged 3-9 Months in Midwife Private Practice Zaenab in Sembung Hamlet, Tungklur Village, Badas District, Kediri Regency: Efektifitas Massage dan Baby SPA (Swim) terhadap Kesesuaian Perkembangan Bayi Usia 3-9 Bulan di Bidan Praktik Mandiri Zaenab di Dusun Sembung, Desa Tungklur, Kecamatan Badas, Kabupaten Kediri - Ertiana, Dwi; Miftakhul, Elga Yuspita (Jurnal Kebidanan Midwiferia, 2021)
The period of infant growth and development is a golden period as well as a critical period of development at the age of 0-12 months. It is said to be a critical period because babies are very sensitive to the environment, need nutritional intake, good stimulation for growth and development. This study aims to determine the effectiveness of massage and Baby Solus Per Aqua (swim) on the suitability of the development of infants aged 3-9 months. Observational analytic research design, cross sectional approach. The population is all babies who make visits. The sampling technique used was purposive sampling, a sample of 22 respondents. The study was conducted on August 2–12, 2020 in Sembung Hamlet, Tungklur Village, Badas District, Kediri Regency. The instrument uses KPSP data collection with clinical observation, data analysis using the Mann Witney U test. The results of the study 11 respondents did treatment, the development was appropriate: 7 babies 67%. 11 respondents who did not receive treatment experienced developmental deviations: 6 infants 54%. Statistical tests showed that there was an effect of massage treatment and Baby SPA (swim) on infant development with a p value of 0.019 0.05. Development is influenced by several supporting factors, in infants who do treatment as much as 6 times the development is appropriate. Babies who do not do treatment experience developmental deviations because in addition to stimulation, parenting, mother's knowledge affects the development of babies, the more often babies get stimulation, the more appropriate the baby's developmental achievement will be.